Playing the Stockmarket in Tana Toraja - Thompson, Robyn (The Australian journal of anthropology, 2000)
This paper describes the players and the play in a weekly stockmarket in Tana Toraja. South Sulawesi, where up to 600 buffalo bulls are bought and sold for exorbitant prices by any standards. These prices are partly determined by external, global economic forces. The buffaloes are all intended for sacrifice in elaborate funerals. Although contributed by individuals or families they are conceived as part of mana. the common wealth of tongkonan. the origin houses of the Toraja. Live bulls cannot be given away but are able to be lent in ceremonial exchanges at funerals. After sacrifice, their raw meat is distributed to participants in the funeral in a version of potlatch. Bulls mediate all exchange. apart from mundane commodity exchange, and are liquid assets. A mature black bull is an object of general equivalence able to be exchanged as payment for certain symbolic objects. In the past the production, distribution and circulation of buffaloes, both on the hoof and as meat, were controlled by the nobility. Buffaloes were said to be in finite supply. They derived from the Upperworld and accompanied the ancestors of the Toraja nobility to this world and were replenished through the ritual of the ways of the ancestors. Now the advent of the market has democratised buffaloes. There has been a dispersion of wealth and the power that the bulls embody. Any man—noble, commoner or former slave-who has sufficient cash is able to buy and sell buffaloes: to have a share in the stockmarket. The marketplace has become a new field of power play, one where innovative methods are being found for increasing the supply of buffaloes by importing hundreds of inferior quality buffaloes and by a program of artificial insemination which has been instigated by the local government. In the parlance of Wall Street this is a bull market.